2021
DOI: 10.3390/vaccines9010048
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Receive COVID-19 Vaccination in Japan

Abstract: In the wake of the COVID-19 pandemic, vaccines are being developed by many countries for the safety of their population. However, people of various nations have revealed hesitancy towards being vaccinated, citing reasons such as side effects, safety, a lack of trust in vaccine effectiveness, etc. This study aimed to explore the willingness of people in Japan to be vaccinated or not be vaccinated and the reasons for either decision. A sample of 1100 respondents was drawn from an internet research panel, and a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
300
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(359 citation statements)
references
References 21 publications
43
300
16
Order By: Relevance
“…Although free vaccinations raised COVID-19 VWR from 69.49% to 83.9% for respondents aged over 58 years old, their VWR remained lower than the 18-27 age group for both paid (OR = 0.581) and free vaccinations (OR = 0.456). This finding was counter to previous studies in Japan and the United States, which showed that the elderly had a higher COVID-19 vaccination willingness [4,20]. The COVID-19 VWR of people who had no medical insurance was only half that of those who had medical insurance (OR = 0.496 for the paid vaccine, OR = 0.513 for the free vaccine) even through the COVID-19 VWR of people without medical insurance increased from 56.82% to 71.59% when the vaccine was free.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although free vaccinations raised COVID-19 VWR from 69.49% to 83.9% for respondents aged over 58 years old, their VWR remained lower than the 18-27 age group for both paid (OR = 0.581) and free vaccinations (OR = 0.456). This finding was counter to previous studies in Japan and the United States, which showed that the elderly had a higher COVID-19 vaccination willingness [4,20]. The COVID-19 VWR of people who had no medical insurance was only half that of those who had medical insurance (OR = 0.496 for the paid vaccine, OR = 0.513 for the free vaccine) even through the COVID-19 VWR of people without medical insurance increased from 56.82% to 71.59% when the vaccine was free.…”
Section: Discussioncontrasting
confidence: 99%
“…The COVID-19 VWR was 82.25% for the free vaccine, significantly higher than 73.62% for the paid vaccine, increasing the COVID-19 VWR by 11.72%. For the paid vaccine, the VWR in this study was higher than in similar studies in Japan (65.7%) [4], France (62%), Germany (70%) [18] and the United States (69%) [5], but roughly the same as the Netherlands (73%), Italy (74%) and Portugal (75%); the VWR for the free vaccine was similar to Denmark (80%) [18] and Australia (85.8%) [19].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In Japan a study was conducted in September 2020 that consisted of 1100 respondents. A significantly higher proportion of men were willing to get vaccinated (68.0%) than women (63.2%) The highest willingness to be vaccinated was found among the oldest age group (77.2%) and participants who had chronic diseases (78.4%) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent systematic review of such studies (C. Lin et al, 2021) concludes that perceptions of vaccine safety and effectiveness are 'universally' consistent determinants of COVID-19 vaccine hesitancy (p. 8). Further, surveys which specifically asked COVID-19 vaccine hesitant participants their reason for vaccine refusal or delay consistently report that concerns over safety and efficacy are among the most common reasons given (Callaghan et al, 2021;Fisher et al, 2020;Frank & Arim, 2020;Ruiz & Bell, 2021;Yigit et al, 2021;Yoda & Katsuyama, 2021). Similarly, qualitative research has also highlighted these concerns as reported drivers of COVID-19 vaccine hesitancy among minority and at-risk groups (Lockyer et al, 2020;Momplaisir et al, 2021;Williams et al, 2020).…”
Section: Beliefs About Covid Vaccines and Vaccine Hesitancymentioning
confidence: 99%